Paleomagnetism of the Great Slave Supergroup, Northwest Territories, Canada: the Stark Formation - Bingham, D. K.; Evans, M. E. (Canadian Journal of Earth Sciences, 1976)
Paleomagnetic results from 55 sampling sites throughout the Stark Formation are reported. The known stratigraphic sequence of these sites enables the behaviour of the geomagnetic field in these remote times (1750 m.y.) to be elucidated. Two polarity reversals are identified and these represent potentially useful correlative features in strata devoid of index fossils. One of these is investigated in detail and indicates that behaviour of the geomagnetic field during polarity reversals was essentially the same in the early Proterozoic as it has been over the last few million years. The pole position (145°W, 15°S, dp = 3.5, dm = 6.9) lies far to the west of that anticipated from earlier results, implying further complexity of the North American polar wander curve. Possible alternatives to this added complexity are discussed.